2008
DOI: 10.1186/1475-2840-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced expression of angiogenic growth factors in skeletal muscle and in capillaries of healthy and diabetic mice

Abstract: Background: Diabetes has negative, and exercise training positive, effects on the skeletal muscle vasculature, but the mechanisms are not yet fully understood. In the present experiment the effects of running exercise on the mRNA expression of pro-and antiangiogenic factors were studied in healthy and diabetic skeletal muscle. The responses in capillaries and muscle fibers, collected from the muscle with laser capture microdissection, were also studied separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 50 publications
3
61
2
Order By: Relevance
“…Similarly, the serum VEGF-A levels did not correlate with tumor volume or tumor weight on day 35 post-tumor cell inoculation in our study. VEGF may be secreted from the tumor, platelets and muscle contraction (19,34). Poon et al demonstrated that the serum VEGF165 levels/platelet count ratio correlated significantly with tumor cytosolic VEGF165 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the serum VEGF-A levels did not correlate with tumor volume or tumor weight on day 35 post-tumor cell inoculation in our study. VEGF may be secreted from the tumor, platelets and muscle contraction (19,34). Poon et al demonstrated that the serum VEGF165 levels/platelet count ratio correlated significantly with tumor cytosolic VEGF165 (33).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Furthermore, it has been shown that training also induce modifications of VEGF mRNA and protein expression. [12][13][14][15][16] Chronic pathological conditions, such as Chronic Obstruction Pulmonary Disease (COPD) and diabetes, 17,18 induce capillary rarefaction suggesting that VEGF is also important in the maintenance of adult skeletal muscle microvasculature. Indeed, the study of Tang et al 19 have implicated VEGF as an essential survival factor for basal skeletal muscle capillarization.…”
Section: Angiogenesis Muscle Plasticity and Muscle Homeostasismentioning
confidence: 99%
“…Angiogenic growth factors enhance neovascularization in patients with limb ischemia 15 . Diabetes is associated with micro-and macrovascular abnormalities in some tissues leading to retinopathy, nephropathy and/or neuropathy and is a risk factor for peripheral vascular disease 16,17 . The present study showed reduced serum concentrations of NO and VEGF after induction of diabetes.…”
Section: Discussionmentioning
confidence: 99%